The vibrational relaxation of CO2 isolated in solid argon: Spectroscopy in Cryocrystals and Matrices - Cenian, A.; Grigorian, G.; Śliwiński, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
For description of the vibrational relaxation of CO2 molecules embedded in Ar matrix themodel based on multiphonon transitions is applied. Rates for the VT and VV processes are determined from a fitting of simulated and experimental data. The calculations confirmed that radiativeprocesses influence significantly the vibrational energy relaxation of CO2 embedded in solid Ar,e.g., the determined rate for energy transfer between n3 and n2. mode is significantly lower than that predicted under assumption of the nonradiative relaxation.